Reduced avoidance behaviour in Daphnia magna due to agrochemical-induced vulnerability - María Eugenia López-Valcárcel; Ana del Arco; Cristiano V.M. Araújo; Gema Parra (Ecotoxicology and Environmental Safety)
The continuous discharge of agrochemicals used in intensive agriculture contaminates aquatic systems, harming aquatic biota and their processes. Although mobile organisms can avoid continuous exposure by moving to less-affected habitats, their capacity can be altered by pollutant exposure. Populations with a previous disturbance history, which show a lower ability to respond to subsequent stressors, are defined as vulnerable. Therefore, this study investigated the so far unknown escape capacity of a vulnerable zooplankton population previously exposed to a contaminated environment. To this end, agrochemically driven vulnerability was induced in populations of Daphnia magna by exposure to sublethal concentrations of glyphosate. Vulnerability was verified using a starvation test in which significant differences were observed between the control populations and populations with a disturbance history. Both the Control and Vulnerable populations were assessed for their avoidance capacity by exposing them to a glyphosate gradient using a Heterogeneous Multiple-Habitat Assay System (HeMHAS). The control populations showed a rapid reaction from the beginning of the assay, with avoidance rates increasing over 24 h, while vulnerable populations were unable to avoid contaminated habitats for up to 24 h. Therefore, we concluded that vulnerable populations have a lower capacity to avoid contaminated habitats. In heterogeneously contaminated habitats, a lower avoidance capacity is responsible for the differential spatial distribution of the affected species, which impacts the ecosystem structure. Additionally, agrochemically induced vulnerability and its effect on avoidance behaviour may affect ecosystem functioning through the altered spatial distribution of zooplankton populations.